Alan Paton a biography - Alexander, Peter (Oxford Univ. Press, 1994)
Alan Paton is best remembered as the author of Cry, the Beloved Country, the most lyrical and moving plea for racial reconciliation to have come out of South Africa this century. His reputation, however, extends far beyond the fields of fiction and literature, for in addition Paton was a teacher, prison reformer, and politician whose achievements have ensured him a lasting place in the troubled history of his country. This is a rich and fascinating story, told against the backdrop of profound political changes in a country that still struggles to achieve the harmony Paton strove for; Paton's own greatness can now be seen for the first time to arise from moral struggles no less profound.